26.48% efficient and stable FAPbI3 perovskite solar cells employing SrCu2O2 as hole transport layer. Issue 3 (11th January 2023) - Noman, Muhammad; Shahzaib, Muhammad; Jan, Shayan Tariq; Shah, Syed Nasir; Khan, Adnan Daud
Abstract : The effect of carbon and copper based charge transport layers on the behavior and performance of FAPbI3 perovskite solar cells was investigated with SrCu2 O2 /FAPbI3 /PCBM structure outperforming others and achieving 26.48% efficiency. Abstract : In general, formamidinium lead tri-iodide (FAPbI3 ) based perovskite solar cells are more stable than their methylammonium lead tri-iodide (MAPbI3 ) counterparts. However, when it comes to power conversion efficiency (PCE), MAPbI3 solar cells are far better. This work aimed to enhance the power conversion efficiency of FAPbI3 solar cells without compromising their thermal stability. The numerical analysis of 6 different proposed structures with 2 carbon based electron transport materials (C60, PCBM) and 3 copper based hole transport materials (SrCu2 O2, CuSCN, CuSbS2 ) is performed using SCAPS-1D software. The parameters are used from various theoretical and experimental published works. In order to investigate the performance of each proposed structure, the defect density, layer thickness and doping concentration of the absorber layer, electron transport layer (ETL) and hole transport layer (HTL) are varied, and optimized parameters are enumerated. The best simulation result having PCE of 26.48% is achieved with 1.25 V open circuit voltage ( V OC ), 23.51 mA cm −2 short circuit current ( J SC ) and 89.5% fill factor (FF) for FTO/PCBM/FAPbI3 /SrCu2 O2 /Au. The proposed structure also showed good thermal stability at 300 K. Moreover, the effects of the different charge transport layer on the energy band alignment, electric field, recombination and IV characteristics are also investigated in detail.